2021
DOI: 10.1007/s11356-021-17009-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to air pollutants and the risk of inflammatory bowel diseases visits

Abstract: BackgroundThe topic of in ammatory bowel disease (IBD) has attracted more and more attentions. Accumulating evidence suggests that exposure to air pollutants is associated with IBD, yet the results are inconsistent and study about daily exposure is few. This study evaluated the association between daily air pollution and IBD in Hefei, China. MethodsDaily IBD admission data were obtained from two hospitals in Hefei from January 1, 2019 to December 31, 2019. Daily concentrations of major air pollutants were prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
10
1
1
Order By: Relevance
“…2 To date, the change in the trend of IBD prevalence in paediatric patients has been reported in observational studies; however, it has not been clearly demonstrated for Asian countries, which are facing issues such as consumption of processed meat, pollution, extreme heat and climate changes. [3][4][5] In South Korea, equitable access to healthcare is uniformly provided across the nation through its characteristic universal health coverage. 6 The contextual background of Korea provides a unique opportunity to observe trends in IBD epidemiology, including treatment patterns and prognostic differences at a population level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 To date, the change in the trend of IBD prevalence in paediatric patients has been reported in observational studies; however, it has not been clearly demonstrated for Asian countries, which are facing issues such as consumption of processed meat, pollution, extreme heat and climate changes. [3][4][5] In South Korea, equitable access to healthcare is uniformly provided across the nation through its characteristic universal health coverage. 6 The contextual background of Korea provides a unique opportunity to observe trends in IBD epidemiology, including treatment patterns and prognostic differences at a population level.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of IBD is multifactorial and includes genetic and environmental factors 2 . To date, the change in the trend of IBD prevalence in paediatric patients has been reported in observational studies; however, it has not been clearly demonstrated for Asian countries, which are facing issues such as consumption of processed meat, pollution, extreme heat and climate changes 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…There was a low level of heterogeneity between the studies in both overall and subgroup analyses. Although the meta-analysis of three studies on air pollution was not performed [ 27 , 51 , 52 ], all three of the studies reported a significant positive correlation between air pollutants and exacerbation of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only 6 out of 20 studies reported information on the duration of IBD morbidity, location of lesions, or medications administered [ 20 – 24 , 50 ]. Moreover, 7 out of 20 studies did not report the number of patients who experienced IBD exacerbations [ 18 , 20 , 26 , 27 , 49 , 51 , 52 ], and 6 of the 11 studies reported different numbers of patients and cases of exacerbations [ 19 , 21 , 22 , 25 , 48 , 50 ]. The abovementioned factors might have resulted in the underestimation or overestimation of the pooled estimate results of the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation